Application of the "Open‐Y" technique in recipient perforator vessels: A comparison study between "Open‐Y" and conventional end‐to‐end anastomosis in terms of postoperative complications. Issue 6 (10th February 2021) - Scaglioni, Mario F.; Meroni, Matteo; Fritsche, Elmar
Abstract: Background: Over the last few years, the increasing employment of perforators as both donor and recipient vessels for free flap tissue transfer lead the surgeons to perform increasingly smaller anastomosis. Size discrepancy is a common problem that might affect the patency rate. This has many implications in the outcome of the procedure and the "Open‐Y" technique might be useful to perform an easier anastomosis by using a bifurcation area. Patients and Methods: Between April 2018 and April 2020 a total of 98 patients who received a free tissue transfer reconstruction throughout the body were retrospectively recruited. The "Open‐Y" technique of anastomosis was used in the recipient artery of 40 perforator‐based flaps, while in 58 cases a conventional anastomosis with nonperforator vessel was performed. The size discrepancy rate and the arterial anastomotic site‐related complications were evaluated and compared. Results: The flap success rate was 100% (40/40) in the "Open‐Y" group, slightly better than the conventional group (96.5%; 56/58) despite a higher size discrepancy rate in the "Open‐Y" group (27.5%; 11/40) compared to the conventional one (12%; 7/58) ( p value, .053). The rate of complications was different, too. Better results were obtained in the "Open‐Y" group with 4/40 (10%) complications compared to the 18/58 (31%) of the conventional group ( p value, .013). Conclusions: The "Open‐Y" technique is a simple and interesting procedure to increase the vessels' diameter thus reducing size discrepancy and increasing the reliability of the anastomosis. This is extremely valuable in the perforator‐to‐perforator free tissue transfer setting where surgeons are often forced to work in a supermicrosurgical field. Every time a suitable bifurcation is encountered this might be a useful procedure to increase the end‐surface available for the anastomosis or to reduce vessels size discrepancy.